Pengaruh Transformasi Digital Terhadap Perilaku Nasabah dalam Penggunaan Fitur Paperless Onboarding : pada Nasabah Bank Syariah Indonesia KCP Panorama Bengkulu - Anisa Nurhasanah; Yosy Arisandy; Miko Polindi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the effect of digital transformation on customer behavior in using the paperless onboarding feature at Bank Syariah Indonesia (BSI) Panorama Branch, Bengkulu. The method used was a quantitative questionnaire, with 94 respondents who were BSI Mobile application users. Data analysis used SPSS with a simple linear regression test. The results showed that digital transformation significantly influenced consumer behavior, with a significance value of 0.000 (<0.05) and a coefficient of determination (R Square) of 0.700. This indicates that 70% of consumer behavior factors are influenced by digital transformation, while 30% are influenced by factors outside the study.